Pelatihan Desain Kemasan Produk yang Menarik Pada PT Mond Nature Lestari - Sudirman, Wahyu Febri Ramadhan; Priyatno, Arif Mudi; Lasepa, Wanda; Afrinis, Nur; Rizqi, Eka Roshifita (Global Sustainability Research Institute, 2024)
Product packaging design training for PT Mond Nature Lestari using Canva aims to improve the design skills of the internal team in creating attractive and professional packaging for moringa leaf-based products, such as moringa floss, moringa chocolate, moringa tea, and moringa coffee. Through this training, participants were introduced to the Canva interface and various design elements, and learned to apply good graphic design principles in packaging creation. The results of the training showed that the updated packaging design not only improved the visual appeal of the product but also supported the company's goals in promoting sustainability and innovation. With the use of Canva, the team was able to create designs quickly and efficiently, saving time and costs, and increasing efforts in responding to market needs. This training also made a significant contribution to increasing the company's competitiveness in the market, strengthening brand identity, and meeting consumer expectations for high-quality products.